Clinical Update on Osteoporosis. (14th March 2019) - Anthamatten, Angelina; Parish, Abby
Abstract: Osteoporosis is described as a silent disease prior to fracture, and the sequelae of an osteoporotic fracture can be devastating. Primary care providers should routinely assess and remediate bone health during wellness visits for women aged at least 50 years. Assessment includes review of a variety of risk factors, bone density testing, and an online fracture risk assessment tool calculation. Diagnosis is based on bone density score and clinical risk factors. Evidence‐based nonpharmacologic therapies are important adjuncts of care, and pharmacologic intervention may also be recommended. A variety of pharmacologic options are available for women with postmenopausal osteoporosis, and it is important to weigh benefits and risks. Pharmacologic indications, therapeutic variations among products, adverse effect profiles, administration considerations, and cost are addressed. Once pharmacotherapy is initiated, duration and drug holidays should also be considered. In general, medication benefits fade when treatment stops, so health care providers should be prepared to routinely revisit therapy indicators that will help define risk and guide treatment decisions. A comprehensive approach to bone health can make a valuable difference in the health of women.